Silviculture Effect in Community Forestry in KPHL VIII Batutegi to Farmers Income and Soil Fertility - Yanyan Ruchyansyah; Christine Wulandari; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2018)
Sekampung Hulu watershed that is located in Batutegi Forest Management Unit (KPH) is one of Watershed priority due to the most area has been cultivated by the community. 59% of the community cultivate the forest area have acquired community forest utilization license (IUPHKm). The objective of the license is so that the community could return the forest function at the same time increasing their prosperity. Agroforestry was silviculture system that is believed as the most appropriate mean to realize those objectives. This research was aimed to figure out the silviculture system done by the farmers in KPHL VII Batutegi and its relation with income increasing and soil fertility. Data collection was conducted on August-September 2016 in Batulima Resort KPHL VIII Batutegi, through interview method of 98 respondents of two Gapoktan (farmers group) that have IUPHKm. The research result showed that there is no significantly correlation between IUPHKm appropriations with the change of silviculture system. There was a negative influence of silviculture system to soil fertility and farmer income. Monoculture system on the IUPHKm area provide the highest income. It was influenced by the duration of forest land utilization that has reached 4,2 years in average, therefore harvesting has been done. The other influence factor was fertilization intensity, so that the plantation would be more productive. Keywords: community forest, farmers' income, silviculture, soil fertility